2013
DOI: 10.1111/ecot.12022
|View full text |Cite
|
Sign up to set email alerts
|

The impact of minimum wages on employment of low‐wage workers

Abstract: This study provides empirical evidence on the impact of a minimum wage increase on employment of workers in the formal sector who have wages below the minimum level in Vietnam. Using the difference‐in‐differences with propensity score matching and the Vietnam Household Living Standard Surveys of 2004 and 2006, the article finds that the minimum wage increase in 2005 reduced the proportion of workers having a formal sector job among low‐wage workers. Most workers who lost formal sector jobs became self‐employed. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 78 publications
0
7
0
1
Order By: Relevance
“…Based on our own fieldwork experience and survey data, and combined with the definition of the Vietnam informal sector introduced by Cling et al (2010) and Nguyen (2010), five types of income-earning activities are identified at the household level namely farmers (self-employment in household agriculture, including crop and livestock production and other related activities); business operators (those who own non-farm household businesses); informal wage earners (paid jobs that are often casual, low paid and often require no education or low education levels. Informal wage earners are often manual workers who work for other individuals or households without a formal labour contract); formal wage earners (paid jobs that are regular and relatively stable in factories, enterprises, state offices and other organizations with a formal labour contract and often require skills and higher levels of education); and finally non-labour income earners (those earn their income from non-labour sources).…”
Section: Methodsmentioning
confidence: 99%
“…Based on our own fieldwork experience and survey data, and combined with the definition of the Vietnam informal sector introduced by Cling et al (2010) and Nguyen (2010), five types of income-earning activities are identified at the household level namely farmers (self-employment in household agriculture, including crop and livestock production and other related activities); business operators (those who own non-farm household businesses); informal wage earners (paid jobs that are often casual, low paid and often require no education or low education levels. Informal wage earners are often manual workers who work for other individuals or households without a formal labour contract); formal wage earners (paid jobs that are regular and relatively stable in factories, enterprises, state offices and other organizations with a formal labour contract and often require skills and higher levels of education); and finally non-labour income earners (those earn their income from non-labour sources).…”
Section: Methodsmentioning
confidence: 99%
“…Gindling and Terrell (2007) also report a negative impact on employment in the formal sector in Costa Rica. Similarly, Nguyen (2010) finds that minimum wage increases led to a decrease in formal employment among low-wage formal sector workers in Vietnam.…”
Section: Literature Reviewmentioning
confidence: 95%
“…Previous studies show that indeed, workers who lose their formal employment do not necessarily become unemployed but rather they are likely to go into the informal sector (either in self-employment or working in an informal firm) (Loayza et al 2005;Perry et al, 2007;Nguyen 2010). In Indonesia, there are potentially labor movements and other types of interactions between formal and informal sectors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While the literature is abundant in other developing countries (China, Indonesia), studies on the economic impacts of minimum wages in Viet Nam are relatively few in number. Using the basic difference-in-difference framework, Nguyen (2013) finds statistically significant negative employment effects in formal sectors but no evidence of adverse effects on overall employment. Nguyen (2014) assesses employment-level effects from a fixed effects approach.…”
Section: Introductionmentioning
confidence: 95%
“…First, I explore the differences in the effect of minimum wage changes on employment and wages across firms with different employment sizes-micro firms and SMEs-in a developing country setting. Second, I provide more detailed evidence of the effects of minimum wage changes in Viet Nam than in the existing studies (Nguyen 2013(Nguyen , 2014, using employer-employee matched data.…”
Section: Introductionmentioning
confidence: 99%